Nickel-decorated single vacancy phosphorene – A favourable candidate for hydrogen storage. (5th August 2021) - Ramachandran, Shreyas; Sai Srinivasan, K.V.; Sujith, Ravindran
Abstract: This work studies the effect of nickel decoration on the hydrogen adsorption properties of single vacancy (SV) defective phosphorene. First principles simulations of Ni decoration show that the SV defective surfaces relax to a doped-like structure with the Ni atom in the place of the vacant phosphorus atom. The functionalised surface shows excess negative charge on neighbouring P atoms, making it suitable for sensing purposes. Additionally, the chemical activity of Ni is reduced due to strong bond formation with phosphorus. Both Ni-decorated SV phosphorene systems have H2 adsorption energies more than 3 times than that of defective phosphorene, with values between −0.594 eV and −0.6 eV. The adsorption mechanism of H2 is a two-fold process involving a small charge transfer from the surface P atoms and weak dipole-dipole interactions between the H2 molecule and the Ni atom, as the reduced chemical activity of Ni prevents bond formation with H2 . The results demonstrate Ni-decorated SV Phosphorene as a promising candidate for Hydrogen storage and gas sensing applications. Further, decoration on defective phosphorene surfaces can be regarded as a method to control the chemical activity of transition metals for use in applications such as catalysis. Highlights: Nickel decoration on SV defective surfaces relaxes to doped structure. Ni decorated SV surfaces have excess negative charge on P atoms. Hydrogen adsorption energy increases by 3.6 times to −0.599 eV in Ni-SV 5/9. Two-step H2 adsorption mechanism – charge transfer and dipole-dipole interaction.